(untitled) (Research, Society and Development, 2021)
The foraging activity of bees is the act of seeking and collecting floral resources (pollen, nectar and water) that are essential for their survival. This activity can be influenced by climatic factors. In this context, the objective of this work was to understand the foraging behavior of Africanized bees Apis mellifera and its relationship with environmental factors. The study was carried out at the teaching unit of the IFPI campus Cocal, city of Cocal-PI. The collections were carried out in the first half of 2021. Five hives were evaluated, and the number of bees that entered carrying pollen and nectar/water in their corbicles was recorded, from 6:00 to 17:00. The hives were observed for 10 minutes every hour, and climate data were recorded at the same time using a thermohygrometer. The bees preferred to collect pollen between 6:00 and 12:00. The pollen foraging activities peaked at 8:00 am in March 2021. The bees collected nectar throughout the day, increasing its frequency between 1:00 pm and 4:00 pm during the period evaluated, with the peak being collection of nectar at 12:00h in June2021.